Radar didn't show tornado (Raton, NM Raton Range, 1996)
Article is about the National Weather Service in Albuquerque not being able to detect the tornado that his Cimarron, New Mexico.
Newspaper article + Photographs 1)Cimarron residents cleanup 2)Volunteers from Philmont Scout Ranch
Mater List Item # 79
File location is in the New Mexico File Cabinets
Keywords: Liles, Charlie -- Weather Service Area Manager; Domenici, Pete -- United State Senator; National Weather Service; Cannon Air Force Base; Department of Commerce; Cimarron Police Department; Capulin Volcano National Monument; Philmont Scout Ranch; Doppler Radar; Tornados; Tornado Injuries; Weather Detection; Tornado Detection; Cimarron, New Mexico; Clovis, New Mexico; Pueblo, Colorado; Maxwell, New Mexico -- Tornado Injuries -- 1964; Wagon Mound -- Tornado Injuries -- 1930